Music at Workplace: Is it trully Improving Employees’ Performance? - Serpian Serpian; Salam Fadillah Alzah; Jusnawati Jusnawati; Kristin Handayani (Universitas Negeri Makassar, 2022)
The purpose of this study was to compare the performance of employees who listened to music while working to those who did not. This study was conducted at the Business Simulation Laboratory, Department of Business Administration of Ujung Pandang State Polytechnic. This study employed an Experimental Research Method with a quantitative methodology. The total participants, 94, were divided into 2 groups, employees with treatment (listening to the music while working) 48 and employees without treatment, with 46 participants. The study's empirical findings indicated that there were productivity differences between employees who got the treatments (listening to music while working) compared to those who did not. The employee who works with music in the workplace performed a more excellent average performance than those who work without music. Listening to favorite songs encourages employees to improve their work efficiency.